Carbon footprint of alternative protein sources for Atlantic salmon (Salmo salar) aquaculture: A two-step systematic literature review - Javier Cantillo; Paritosh C. Deshpande (Aquaculture Reports)
Atlantic salmon (Salmo salar) is the most important species in marine aquaculture in terms of production volume, and it is regarded as a remarkable example of the industry’s development. Yet, its importance is expected to grow manifolds in the future, and to ensure its expansion in a sustainable way, alternative feed ingredients are needed. In this study, we used systematic literature reviews as a research method to identify recent potential alternative protein sources for Atlantic salmon aquaculture and to determine the hotspots of the carbon footprint of these proteins. The findings according to the volumes of papers reviewed in the literature, revealed a strong interest in the recent literature on insect and single-cell proteins, both in their effects on Atlantic salmon aquaculture and their carbon footprint analysis. Both protein groups have emerged in the literature as suitable replacements for more traditional diets. Furthermore, studies assessing their carbon footprint revealed that activities such as the production of the substrates/feed/fertilizer used in cultivation/rearing, as well as the energy required for production or processing stages, are the most significant contributors to the carbon footprint. Other types of protein sources studied in the literature included marine proteins, terrestrial animal by-products, and plant-based proteins. For each protein type and its identified alternatives, we analysed the implications of their carbon footprint performance findings and discussed future opportunities and prospects.